Large Scale Synthesis of Three‐dimensional Hierarchical Porous Framework with High Conductivity and its Application in Lithium Sulfur Battery - Wang, Xu‐Ri; Wang, Xiao; Xu, Xu‐Peng; Wu, Ya‐Qin; Lei, Wei‐Xin; Zou, You‐Lan; Ma, Zeng‐Sheng; Pan, Yong (Chemistry : a European journal, 2021)
Quick capacity loss due to the polysulfide shuttle effects and poor rate performance caused by low conductivity of sulfur have always been obstacles to the commercial application of lithium sulfur batteries. Herein, an in‐situ doped hierarchical porous biochar materials with high electron‐ion conductivity and adjustable three‐dimensional (3D) macro‐meso‐micropore is prepared successfully. Due to its unique physical structure, the resulting material has a specific surface area of 2124.9 m2 g−1 and a cumulative pore volume of 1.19 cm3 g−1. The presence of micropores can effectively physically adsorb polysulfides and mesopores ensure the accessibility of lithium ions and active sites and give the porous carbon material a high specific surface area. The large pores provide channels for the storage of electrolyte and the transmission of ions on the surface of the substrate. The combined effect of these three kinds of pores and the N doping formed in‐situ can effectively promote the cycle and rate performance of the battery. Therefore, prepared cathode can still reach a reversible discharge capacity of 616 mAh g−1 at a rate of 5 C. After 400 charge–discharge cycles at 1 C, the reversible capacity is maintained at 510.0 mAh g−1. This new strategy has provided a new approach to the research and industrial‐scale production of adjustable hierarchical porous biochar materials. Tremella is utilized as the precursor, a new process method (high‐shear, freeze‐drying and chemical activation are used in turn) is proposed, and an in‐situ doped hierarchical porous biochar materials with adjustable 3D macro‐meso‐micropore is prepared successfully. Due to its unique physical structure, prepared cathode can still reach a reversible discharge capacity of 616 mAh g−1 at a rate of 5 C. After 400 charge‐discharge cycles at 1 C, the reversible capacity is maintained at 510.0 mAh g−1.